In silico structural exploration of serine protease from a CTG-clade yeast Meyerozyma guilliermondii strain SO - Lorrine, Okojie Eseoghene; Raja Abd Rahman, Raja Noor Zaliha; Tan, Joo Shun; Salleh, Abu Bakar; Oslan, Siti Nurbaya (Elsevier, 2023)
In eukaryotes, serine proteases are cellular localized hydrolases reported to regulate essential biological reactions. Improved industrial applications of proteins are aided by prediction and analysis of their 3-dimensional structures (3D). A serine protease was identified from CTG-clade yeast Meyerozyma guilliermondii strain SO and its 3D structure as well as its catalytic attributes have not been fully understood yet, thus we seek to report on the catalytic mechanism of M. guilliermondii strain SO MgPRB1 using substrate PMSF via in silico docking as well as its stability by way of disulfide bonds formation. Herein, bioinformatics tools and techniques were used to predict, validate and analyze the possible changes of CUG ambiguity (if any) in strain SO using template PDB ID: 3F7O. Structural assessments confirmed the classic catalytic triad Asp305, His337, and Ser499. Superimposition of MgPRB1 and template 3F7O structures revealed the unlinked cysteine residues between Cys341, Cys440, Cys471 and Cys506 of MgPRB1 compared to template 3F7O with two disulfide bonds formation, which confers structural stability. In conclusion, serine protease structure from strain SO was successfully predicted and studies towards understanding at the molecular level may be undertaken for its potential applications in the degradation of peptide bonds.